Integrated Pest Management (IPM) in Agriculture and Its Role in Maintaining Ecological Balance and Biodiversity - Prodipto Bishnu Angon; Sujit Mondal; Israt Jahan; Mitu Datto; Uttam Biswas Antu; Famin Jahan Ayshi; Md. Shafiul Islam (Advances in Agriculture)
The production of sustainable crops and environmental management in farming face several significant potential obstacles, including climate change, resource depletion and environmental degradation. Weeds and insect pests that considerably reduce yields have put crop production systems in danger. The greatest worry for farmers is the decline in productivity due to illnesses and pests. Insects, weed pests, and plant pathogens destroy more than 40% of all potential food production every year. The widespread use of integrated pest management (IPM) is a result of worries about the long-term viability of conventional agriculture. IPM ensures sufficient, secure, equitable, and steady flows of both food and ecosystem services, as well as increased agricultural profitability due to lower pest management expenditures. A number of studies conducted on IPM have been combined. Important information from all these studies was analyzed and summarized in this literature review. In this article, we investigated the following: (1) explanation of different management components; (2) development in organically integrated weed and insect pest management, with possible ramifications and scope; (3) knowledge and adaptation status of IPM in the modern world; (4) resources and tools of IPM; (5) current challenges and suggested future research priorities. Regular training related to IPM should be arranged to spread the knowledge of IPM to all farmer levels. This requires the cooperation of the government. Furthermore, IPM will reach a new milestone if Internet of Things technology is practiced along with the existing pest control method. Overall, this review addresses the possibilities for researchers and farmers to use a variety of natural control agents as a full or partial replacement for synthetic pesticides.